Unidad, la voz de las clases desprotegidas: los vaivenes políticos de un periódico comunista y su discurso social sobre los problemas del campesinado y los sindicatos (1960-1965) - Malpartida, Marcos Marcial Matos (2022)
The objective of this research is to analyze the discourses of the Unidad newspaper, in the face of the great social problems of the agrarian and labor unions. In the period examined here (1960-1965), the first partial Agrarian Reform was carried out in southern Peru, which represented a first victory for the agrarian unions. However, Peru in those years was governed by four presidents: two of them elected democratically, but with governments that violated the rights of peasants and workers; and two military presidents. The militants of the PCP and the Unidad newspaper were favorite targets of persecution and arrests, however, they managed to publish some numbers. During 1962 and 1963, Unidad focused primarily on elections and competed against the commercial newspapers La Prensa and La Tribuna, the official newspaper of the Peruvian Aprista Party. In addition to the difficult political and social situation in Peru, the Peruvian Communist Party also faced internal divisions. The distance between the Chinese Communist Party (CPCH) and the Communist Party of the Soviet Union (PCUS) caused deep divisions in Peru. In 1964 the Peruvian Communist Party was divided into two: the Partido Comunista Peruano - Unidad (PCP-U) and the Partido Communista Peruano – Bandera Roja (PCPBR), with the division of the party appeared the Bandera Roja newspaper of Maoist ideology, this newspaper would become the main rival of Unidad, disputing the representation of the agrarian and labor unions.